2016
DOI: 10.4103/2229-3485.179434
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 3% hypertonic saline nebulization in acute bronchiolitis among Indian children: A quasi-experimental study

Abstract: Objective:To compare the effects of 3% hypertonic saline (HS) and 0.9% normal saline with nebulized 0.9% normal saline with salbutamol in patients of acute viral bronchiolitis.Materials and Methods:Participants were divided into three groups, that is, 3% HS group, 0.9% normal saline group and 0.9% saline with salbutamol group. Four doses at interval of 6 h were given daily until discharge. Average CS score and length of hospital stay were compared. One-way analysis of variance paired t-test and Chi-square test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…Several studies [11, 12] concluded that hypertonic saline might promote the sputum induction, reduce the incidence of complications, while Huang et al [13, 14] found that hypotonic saline nebulization might be superior over isotonic saline in maintaining the airway patency and reducing pulmonary infection for patients with tracheostomy, interestingly, a recent study [15] found that hypertonic and isotonic saline nebulization offered no significant efficacy difference in patients with tracheostomy. So far, no studies have been performed to directly compare the efficacy of hypotonic, isotonic and hypertonic saline nebulization in clinic and lab settings.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [11, 12] concluded that hypertonic saline might promote the sputum induction, reduce the incidence of complications, while Huang et al [13, 14] found that hypotonic saline nebulization might be superior over isotonic saline in maintaining the airway patency and reducing pulmonary infection for patients with tracheostomy, interestingly, a recent study [15] found that hypertonic and isotonic saline nebulization offered no significant efficacy difference in patients with tracheostomy. So far, no studies have been performed to directly compare the efficacy of hypotonic, isotonic and hypertonic saline nebulization in clinic and lab settings.…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of the patients in our study population was 9.9 ± 6.2 months (as compared to Gupta et al in which mean age at presentation was 5.7±3.4 months), the youngest being 2 months and the eldest being 24 months. 6 In our study, most of the children 115(46.5%) presented are in 7-12 months of age. The mean age observed by Sarrell et al is 12.5±6 months (range, 3-24 months), 7 Mandelberg et al is 2.9±2.1 months (range, 0.5-12 months), 8 Tal et al is 2.6±1 months (range, 1-5 months) and Kuzik et al is 4.7±4.2 months (range, 10 days to 18 months).…”
Section: Discussionmentioning
confidence: 49%
“…In the previously reported clinical studies , the device was not specified in 11 cases, the MMAD in 12 cases, the aerosol output rate in 16 cases, and the gas vector in 16 cases. Because some studies [12,16,17,21,25] have used, like ours, nebulizations with air and have reported no side effects, the influence of the gas vector on the 3% HS tolerance is inconclusive. In our study, a higher proportion of adverse events were noted with the mesh nebulizer, maybe because of its high aerosol output rate that may favor cough and respiratory trouble.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies looking, like ours, for a clinical effect, only few adverse events were reported, with nebulizations of 3% HS considered as safe and very well tolerated in in-patients with acute bronchiolitis [12][13][14][15][16][17][18][19][20][21][22][23][24][25] . Only 2 studies described a high rate of adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation